Relevance of Sociodemographic Status to the Potential for Perinatal Depression Post-Natural Disasters - Rafika Oktova; Chun Hoe Tan (PT. Riset Press International, 2026)
Indonesia is one of the countries at high risk of disasters due to its geographical and geological conditions. Based on the 2022 Indonesian Disaster Risk Index measurement, West Sumatra Province is included in the high-risk category with a value of 144.39, indicating a high disaster threat, namely earthquakes, tsunamis, volcanoes, floods, landslides, droughts, extreme weather, extreme waves and abrasion, and forest and land fires. The effects of natural disasters can trigger an increase in depressive symptoms during and after pregnancy, which is a serious threat to global public health. WHO data from 2024 show that almost 300 million people need humanitarian assistance, with an increased risk of mental health issues in disaster-affected populations. This study aimed to analyze the relationship between socio-demographic status and the potential incidence of perinatal depression post-natural disasters in West Sumatra. This is an analytical observational study with a cross-sectional approach conducted in Agam Regency, Tanah Datar Regency, and Padang City. Data collection was carried out in October-December 2024. The sample comprised 23 pregnant women, selected using purposive sampling. The research instrument used was the Edinburgh Postnatal Depression Scale (EPDS) Questionnaire. Data were analyzed univariately and bivariately with the Chi-Square test with a significance level of α = 0.05. The results of this study showed that 52% of pregnant women experienced perinatal depression. The bivariate analysis yielded significant values for the variables: age p = 0.001), education p = 0.001), occupation p = 0.003), parity p = 0.036), family income p = 0.009), and history of miscarriage p = 0.007). It was concluded that all these variables were related to the potential for perinatal depression in pregnant women post-natural disasters in West Sumatra, Indonesia. Socio-demographic factors are very important to pay attention to in pregnant women, in order to reduce the risk of perinatal depression after natural disasters through routine health education programs by health workers.